Predicting circRNA–Disease Associations Based on Improved Collaboration Filtering Recommendation System With Multiple Data - Lei, Xiujuan; Fang, Zengqiang; Guo, Ling (Frontiers in Genetics, 2019)
With the development of high throughput techniques, various biological molecules are discovered, which includes the circular RNAs (circRNAs). circRNA is a novel endogenous noncoding RNA which play significant roles in regulating gene expression, moderating the microRNAs transcription as sponges and diagnosing diseases and so on. Based on the circRNA particular molecular structures which are closed loop structures with neither 5′-3′ polarities nor polyadenylated tails, circRNAs are more stable and conservative than the normal linear coding or noncoding RNAs, which makes circRNAs could be a biomarker of various diseases. Although some conventional experiments are used to identify the associations between the circRNAs and diseases, almost of the techniques and experiments are time-consuming and expensive. In this study, we propose a collaboration filtering recommendation system based computational method, which handles the ‘cold start’ problem to predict the potential circRNA-disease associations, which is named ICFCDA. All the known circRNA-disease association data is downloaded from circR2Disease database (http://bioinfo.snnu.edu.cn/CircR2Disease/). Based on these data, multiple data is extracted from different database to calculate the circRNA similarity network and the disease similarity network. The collaborating filtering recommendation system algorithm is first employed prediction circRNA-disease associations. Then, the leave one out cross validation (LOOCV) mechanism is adopted to measure the performance of our proposed computational method. ICFCDA achieves the areas under the curve (AUCs) of 0.946, which is better than other existing methods. In order to further illustrate the performance of ICFCDA, case studies of some common diseases are made and the results are confirmed by other databases. The experimental results show that ICFCDA is competent in predicting the circRNA-disease associations.